Theory of the Pecking Order versus theory of the Trade Off for the company Coservicios S.A. E.S.P (2014)
This paper aims to analyze the degree of application of two theories of capital structure that have been contradictory and extensively compared. For the implementation of the Trade Off theory are used two models, the first proposed by Lopez and de Luna (2002) and the second model to be applied is that proposed by Cruz et al. (2003). For the implementation of the Pecking Order theory is analyzed how stocks have been managed, longterm debt, the growth of net operating assets, the trend that has been operating profitability of assets and EBITDA. At the end you will find that in the periods analyzed the most used theory has been to Pecking Order which has been more empirical evidence in other organizations and that Trade Off theory application was not found.